Evaluation of a Novel Water-Based Automated Endoscope Cleaning Process Compared to Conventional Manual Cleaning for Reducing Duodenoscope Contaminatio - Koen van der Ploeg; Juliëtte A. Severin; Margreet C. Vos; Nicole S Erler; Adriana J.C. Bulkmans; Marco Bruno; Bibi C.G.C. Mason-Slingerland (Endoscopy International Open)
Background and Aims: Duodenoscope contamination remains a persistent problem, exposing patients to infection risks. Automation in reprocessing may limit human error, reduce the workload, and increase uniformity and traceability. However, its effectiveness should be evaluated before implementation. This study assessed the impact of implementing a novel water-based automated endoscope cleaning process on duodenoscope contamination.